Thermal biology and swimming performance of Atlantic cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) - Norin, Tommy (PeerJ, 2019)
Atlantic cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) are two commercially important marine fishes impacted by both overfishing and climate change. Increasing ocean temperatures are affecting the physiology of these species and causing changes in distribution, growth, and maturity. While the physiology of cod has been well investigated, that of haddock has received very little attention. Here, we measured the metabolic response to increasing temperatures, as well as the critical thermal maximum (CT(max)), of cod acclimated to 8 and 12 °C and haddock acclimated to 12 °C. We also compared the swimming performance (critical swimming speed, U(crit)) of cod and haddock at 12 °C, as well as the U(crit) of 12 °C-acclimated cod acutely exposed to a higher-than-optimal temperature (16 °C). The CT(max) for cod was 21.4 and 23.0 °C for 8- and 12 °C-acclimated fish, respectively, whereas that for the 12 °C-acclimated haddock was 23.9 °C. These values were all significantly different and show that haddock are more tolerant of high temperatures. The aerobic maximum metabolic rate (MMR) of swimming cod remained high at 16 °C, suggesting that maximum oxygen transport capacity was not limited at a temperature above optimal in this species. However, signs of impaired swimming (struggling) were becoming evident at 16 °C. Haddock were found to reach a higher U(crit) than cod at 12 °C (3.02 vs. 2.62 body lengths s(−1), respectively), and at a lower MMR. Taken together, these results suggest that haddock perform better than cod in warmer conditions, and that haddock are the superior swimmer amongst the two species.